1999
DOI: 10.1007/s005920050142
|View full text |Cite
|
Sign up to set email alerts
|

Bone metabolism in type 2 diabetes mellitus

Abstract: Several conditions have been described to cause osteoporosis, including diabetes mellitus. While the relationship between type 1 diabetes and osteopenia is well documented in the literature, data on the presence of this complication in type 2 diabetes have not been well established. We studied a population composed of 66 post-menopausal women with type 2 diabetes and a control population. We examined bone mineral density with the dual-energy X-ray absorptiometry (DXA) technique at the lumbar and femoral levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 8 publications
7
61
1
3
Order By: Relevance
“…Furthermore, multiple regression analysis showed that the number of complications was associated with decreased 25-OHD concentrations in type 2 diabetes patients, suggesting that the progress of diabetic microangiopathy is associated with the decrease of serum concentration of 25-OHD. It has been reported that decreased bone mineral content was found in type 1 diabetes patients and insulintreated type 2 diabetes patients, whereas both increased and decreased bone mass were found in type 2 diabetes patients treated without insulin [18,28,29]. In the present study, we showed that serum concentrations of 25-OHD in insulin-treated type 2 diabetes patients were significantly lower than those in type 2 diabetes patients treated with oral hypoglycemic agents and those in patients without medicine.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Furthermore, multiple regression analysis showed that the number of complications was associated with decreased 25-OHD concentrations in type 2 diabetes patients, suggesting that the progress of diabetic microangiopathy is associated with the decrease of serum concentration of 25-OHD. It has been reported that decreased bone mineral content was found in type 1 diabetes patients and insulintreated type 2 diabetes patients, whereas both increased and decreased bone mass were found in type 2 diabetes patients treated without insulin [18,28,29]. In the present study, we showed that serum concentrations of 25-OHD in insulin-treated type 2 diabetes patients were significantly lower than those in type 2 diabetes patients treated with oral hypoglycemic agents and those in patients without medicine.…”
Section: Discussionsupporting
confidence: 47%
“…Both the increase in bone turnover markers and the decrease in bone formation have been reported in diabetic populations [9,18]. It has been reported that impaired vitamin D metabolism exists in spontaneously diabetic GK rats [19], and that chronic insulin-deficiency results in a decrease in 1-α hydroxylase activity and an increase in 24-hydroxylase activity in chronic streptozotocin-induced diabetic rat [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in rodent models of type 2 DM and in rodents fed high-fat diets have demonstrated a reduction in osteoblast recruitment and mineral apposition rate and an increase in osteoclastogenesis, resulting in an imbalance between bone formation and resorption (42,43). Cross-sectional findings in humans further support these data, as serum markers of bone formation, such as osteocalcin, are lower and markers of bone resorption, such as C-terminal telopeptide of type 1 collagen, are elevated in participants with type 2 DM (44,45). Increased bone resorption may be mediated by the formation of advanced glycation end products, which stimulate osteoclast activity and may lead to an uncoupling of bone formation and resorption (46).…”
Section: Pritchard Et Almentioning
confidence: 87%
“…O LDER WHITE WOMEN with type 2 diabetes have higher areal BMD than women without diabetes, even after adjusting for body size, (1)(2)(3)(4)(5) but not much evidence exists for older white men and black adults or for volumetric BMD. Some large studies have found higher BMD among white men with type 2 diabetes, (2,4) but others reported nonsignificant differences.…”
Section: Introductionmentioning
confidence: 99%